Factors Affecting the Anxiety Levels of Health Workers at Budi Kemuliaan Hospital in Managing Covid-19 Patients - Astiti, Chairunnisa; Yuniasih, Dewi; Desvita, Widea Rossi; Safaria, Triantoro (Ahmad Dahlan Medical Journal, 2023)
This study aims to determine the factors that influence the level of anxiety of health workers in handling COVID-19 patients at Budi Kemuliaan Hospital, Batam City. This study uses an observational analytic method and a cross-sectional design with data collection through primary data. The study was conducted in December 2021 – January 2022 at Budi Kemuliaan Hospital Batam City with a research population of 99 health workers who were directly involved in handling COVID-19 patients with a total sample of 91 health workers who met the inclusion criteria and the sampling technique used was total sampling. The research data was taken using a questionnaire and then processed using SPSS. Of 91 respondents, 43 respondents (47.3%) did not experience anxiety, 41 respondents (45.1%) experienced mild anxiety, and 7 respondents (7.7%) experienced moderate anxiety. Based on the results of Kendall's Tau-b analysis, there was no relationship between age, gender, family status, level of knowledge, and availability of PPE on the anxiety level of health workers at Budi Kemuliaan Hospital Batam City (p>0.05). The conclusion is no factors that affect the anxiety level of workers' health. Further research is needed to analyze other factors that influence anxiety with different methods and measuring instruments.